Empyema associated with Lemierre syndrome: case report and literature review - S. Gomez, Ulises; Valdez, Gustavo A. H.; M. Rojas, Jorge; C. Escamilla, Juan A.; Q. Melendez, jocelyn N.; G. Villar, Marco A.; M. Jimenez, Ivan A. (International Journal of Research in Medical Sciences, 2024)
Postanginal septicemia, also called Lemierre syndrome, is a metastatic infection that can have multiple complications, including empyema. Therefore, the natural history of the disease begins with an infection of the oropharynx by microbiota from the digestive system, which causes a thrombophlebitis of the jugular vein with septic infiltrations, including into the lungs causing pneumonia, which in turn can generate parapneumonic effusions and/or empyemas. Furthermore, it is a syndrome that was thought to have been forgotten by the era of antibiotics, but with resistance to these antibiotics it has begun to re-emerge. Next, we will talk about a case of a 41-year-old man with no significant pathological history, who entered secondary to a peritonsillar abscess which turned into Lemierre syndrome with a treatment based on broad-spectrum antibiotics and then performed of lung decortication by thoracotomy. Empyema as a complication of Lemierre syndrome is rare and even more so in this post-antibiotic era, so health personnel should have a high clinical suspicion since adequate and timely treatment will help reduce the complications of this disease, as well as like his mortality.